Multiple Events and Multiple Users Tabulation System with E-Certificate Generation - S. Borcelo, Rowena; D. Siason Jr, Nordy; Cornelio Jr, Benjamin L. (SOTVI, 2025)
This study was conducted to help the Cultural Office of the Iloilo State University of Science and Technology (ISUFST) Dingle Campus by developing a system to make contest tabulation faster and more accurate. The problem is that most of the events or contests still use a paper and pen or manual tabulation. This system is called the MEMU Tabulation System with e-certificate generation, it sends email confirmations to certify that judges were present and participated, ensuring fairness and transparency. The researchers used a developmental research method so the system could be improved in the future based on the needs of the Cultural Office. To make sure it met quality standards, the system was evaluated using the ISO 25010 framework, which checks important aspects like usability, reliability, and functionality. For the evaluation, the researchers asked for feedback from 10 IT experts and 40 users. These users were cultural event coordinators, faculty members, staff, and judges with experience in local pageants. Their opinions were gathered to see how well the system worked and how easy it was to use. The results were very positive. The system earned a score of 4.89, which is considered “Excellent.” This means the MEMU Tabulation System is highly reliable, easy to use, and meets the expectations of its users. It shows that the system can help simplify and improve the way contest results are handled. Overall, the study demonstrates how the MEMU Tabulation System can benefit cultural events at ISUFST Dingle Campus by making the process more efficient, accurate, and fair for everyone involved.